Comment on "The global tree restoration potential" - Lewis,SL; Mitchard,ETA; Prentice,C; Maslin,M; Poulter,B (Science, 2019)
Bastin et al (Reports, 5 July 2019, p. 76) state that the restoration potential of new forests globally is 205 gigatonnes of carbon, conclude that "global tree restoration is our most effective climate change solution to date," and state that climate change will drive the loss of 450 million hectares of existing tropical forest by 2050. Here we show that these three statements are incorrect.